2008
DOI: 10.1159/000153430
|View full text |Cite
|
Sign up to set email alerts
|

Ethical, Legal, and Social Issues in Health Technology Assessment for Prenatal/Preconceptional and Newborn Screening: A Workshop Report

Abstract: Prenatal/preconceptional and newborn screening programs have been a focus of recent policy debates that have included attention to ethical, legal, and social issues (ELSIs). In parallel, there has been an ongoing discussion about whether and how ELSIs may be addressed in health technology assessment (HTA). We conducted a knowledge synthesis study to explore both guidance and current practice regarding the consideration of ELSIs in HTA for prenatal/preconceptional and newborn screening. As the concluding activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 91 publications
0
25
0
Order By: Relevance
“…Regardless of their views on consent, with the exception of one father all parents and health professionals unanimously valued the idea that parents should be fully informed about NBS. 45 As shown in previous research, however, the amount of information needed to achieve this differed between parents, 12,66 even within couples, with parents also differing depending on whether or not they had had previous children. Thus, although there is a uniform ideal goal of being informed, the information needed to achieve this is unlikely to be uniform.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Regardless of their views on consent, with the exception of one father all parents and health professionals unanimously valued the idea that parents should be fully informed about NBS. 45 As shown in previous research, however, the amount of information needed to achieve this differed between parents, 12,66 even within couples, with parents also differing depending on whether or not they had had previous children. Thus, although there is a uniform ideal goal of being informed, the information needed to achieve this is unlikely to be uniform.…”
Section: Discussionmentioning
confidence: 73%
“…12,19,61 Indeed, one paper suggested that information was valued more than choice. 45 Although effective information provision was seen as central to choice 12 and the quality of the choices made, 62 it was also valued for minimising distress if further testing was required or a diagnosis given. 63 In countries that rely on parents actively seeking further care this was improved if parents were given relevant information.…”
Section: Relevant Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although they are usually intended to take a societal or policy perspective, health technology assessments are often limited by a lack of rigorous data on those "nontechnical" issues that may be important in implementation in practice (Potter et al 2009). For example, Lehoux and Blume (2000) describe the Australian experience of a technology assessment process for cochlear implants that focused on the outcome of decibels of hearing loss restored but failed to appreciate the objections of the Deaf community to what they saw as a socially disruptive intervention.…”
Section: Introductionmentioning
confidence: 99%